2012
DOI: 10.1074/jbc.m112.353854
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-coupled Receptor Kinase 5 Phosphorylates Nucleophosmin and Regulates Cell Sensitivity to Polo-like Kinase 1 Inhibition

Abstract: Background: G protein-coupled receptor kinases (GRKs) are important regulators of receptor signaling although little is known about their functions beyond their receptor modifying activities. Results: GRK5 binds and phosphorylates nucleophosmin. Conclusion: GRK5 and polo-like kinase 1 coordinately regulate nucleophosmin phosphorylation and cell sensitivity to inhibitor-induced apoptosis. Significance: GRKs play an important role in regulating normal cell functions such as cell cycle regulation and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…For example, G-protein coupled receptor kinase 5, GRK5, is a member of the family of serine/threonine protein kinases that phosphorylate G protein-coupled receptors as well as nonreceptor substrates. GRK5 was recently shown to phosphorylate Nucleophosmin (NPM1), which is mutated in approximately 28% of AML patients (30,47). We observed that GRK5 is expressed at higher levels in high-risk AML patients compared with low-risk patients (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…For example, G-protein coupled receptor kinase 5, GRK5, is a member of the family of serine/threonine protein kinases that phosphorylate G protein-coupled receptors as well as nonreceptor substrates. GRK5 was recently shown to phosphorylate Nucleophosmin (NPM1), which is mutated in approximately 28% of AML patients (30,47). We observed that GRK5 is expressed at higher levels in high-risk AML patients compared with low-risk patients (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Initial studies revealed that inhibition of Plk1 using the Plk1 inhibitor BI 2536 had no effect on EGF-induced centrosome separation in HeLa cells (Figure 6A) or on the basal level of centrosome separation (data not shown). BI 2536 is a potent Plk1 inhibitor, with K i ≈ 0.5 nM (Steegmaier et al ., 2007), and was previously shown to effectively inhibit centrosome disjunction (Mardin et al ., 2011) and nucleophosmin phosphorylation (So et al ., 2012). To investigate the potential involvement of Nek2A, Nek2A levels were knocked down by siRNA treatment (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, many studies revealed that GRKs have additional functions beyond regulating GPCRs (Gurevich et al ., 2012). For example, GRKs phosphorylate and regulate the function of many additional proteins, including tubulin (Carman et al ., 1998; Pitcher et al ., 1998), NHERF (Hall et al ., 1999), synucleins (Pronin et al ., 2000), phosducin (Ruiz-Gomez et al ., 2000), platelet-derived growth factor and epidermal growth factor receptors (Freedman et al ., 2002), ezrin (Cant and Pitcher, 2005), p38 (Peregrin et al ., 2006), NFκB1 p105 (Parameswaran et al ., 2006), HDAC5 (Martini et al ., 2008), IκBα (Patial et al ., 2009), β-arrestin-1 (Barthet et al ., 2009), p53 (Chen et al ., 2010), Hip (Barker and Benovic, 2012), nucleophosmin (So et al ., 2012), and many others. GRKs have also been linked with a number of diseases, including various neurological disorders (Suo et al ., 2007; Bychkov et al ., 2008, 2011; Garcia-Sevilla et al ., 2010), cardiovascular disease (Ungerer et al ., 1993; Gros et al ., 1997; Huang et al ., 2012), and cancer (Matsubayashi et al ., 2008; Tiedemann et al ., 2010; Kim et al ., 2012; Woerner et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further, simply keeping overexpressed GRK5 out of the nucleus prevents the pathological growth of the heart after hypertrophic stimuli via lower HDAC kinase activity and less MEF2 activation 14 . Since GRK5 has been shown to bind DNA in the nucleus of non-myocytes 10 and shown to interact with other nuclear proteins such as Iκ-Bα, p53 and nucleophosmin 15, 16, 28 , we explored whether GRK5’s role in pathological cardiac hypertrophy, in addition to MEF2 regulation through phosphorylation of HDAC5, may involve other targets and mechanisms.…”
Section: Discussionmentioning
confidence: 99%